2020
DOI: 10.21203/rs.3.rs-31482/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Status and Trends of Mitochondrial Dynamics Research: A Global Bibliometric and Visualized Analysis

Abstract: Objectives: Mitochondria are remarkably dynamic organelles encapsulated by bilayer membranes. The dynamic properties of mitochondria are critical for energy production. Our study aims to investigate the global status and trends of mitochondrial dynamics research.Method: Publications related to the studies of mitochondrial dynamics from 2000 to 2019 were retrieved from Web of Science database. A total of 2999 publications were included. Bibliometric analysis was conducted by visualization of similarities viewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 41 publications
1
38
0
1
Order By: Relevance
“…As we have seen in our evidence maps on the main topics, a large number of articles focused on clinical features studies, pathological findings and therapeutic design, care facilities preparation and infection control, and maternal, perinatal and neonatal outcomes Meanwhile, all these topics have been emerging commonly in recent months and may become a major topic in the next years, particularly after COVID-19 in Wuhan as suggested by a more recent study [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As we have seen in our evidence maps on the main topics, a large number of articles focused on clinical features studies, pathological findings and therapeutic design, care facilities preparation and infection control, and maternal, perinatal and neonatal outcomes Meanwhile, all these topics have been emerging commonly in recent months and may become a major topic in the next years, particularly after COVID-19 in Wuhan as suggested by a more recent study [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, well curated MeSH terms were used as the object of topic analysis in this study, compared with author-selected keywords which were usually chosen by existing COVID-19-related bibliometric analysis. [ 4 7 ] Due to the limited number and randomness of author-selected keywords, the derived results, especially the co-occurrence analysis results, cannot reflect the real status of the COVID-19 research. Our MeSH terms-based methodology could better disclose the research topics and trends of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…However, some of the bibliometric analysis were targeting at coronavirus, not just severe acute respiratory syndrome coronavirus 2 (SARS-COV-2), for the purpose of providing reference for COVID-19 research, and the time window was usually set for a long retrospective duration. [ 4 7 ] For example, Mao et al [ 7 ] analyzed coronavirus articles published from 2003 to 2020. Up to the investigation time of this study, there were limited number of bibliometric studies specific to COVID-19 and most of them were found and implemented at early stage of COVID-19 outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of co-occurrence analysis is to determine the relevance of items according to the quantity of projects that appear together and describe the internal relationships and structure of an academic field, and reveal the research frontiers ( 156 ). The development of scientific research and programs could be monitored and followed closely as popular topics and directions were identified through co-occurrence analysis ( 155 , 157 ).…”
Section: Global Status Of Mitochondrial and Osteoarthritis Researchmentioning
confidence: 99%